Optimum hospice at home services for end of life care: protocol of a mixed methods study employing realist evaluation - Butler, C; Brigden, C; Gage, H; Williams, P; Holdsworth, L; Greene, K; Barclay, S; Wilson, P; Wee, B (BMJ Publishing Group, 2018)
Introduction Hospice at home (HAH) services aim to enable patients to be cared for and die in their place of choice, if that is at home, and to achieve a “good death”. There is a considerable range of hospice at home services operating in England. The published evidence focuses on evaluations of individual services, which vary considerably, and there is a lack of consistency in terms of the outcome measures reported. The evidence therefore does not provide generalisable information, so the question “what are the features of hospice at home service models that work, for whom, and under what circumstances?” remains unanswered. The study aims to answer this question. Methods and analysis This is a mixed methods study in three phases informed by realist evaluation methodology. All HAH services in England will be invited to participate in a telephone survey to enable the development of a typology of services. In the second phase, case study sites representing the different service types will collect patient data and recruit carers, service managers and commissioners to gather quantitative and qualitative data about service provision and outcomes. A third phase will synthesise and refine the results through consensus workshops. Ethics and dissemination The first survey phase has University ethics approval and the second phase, IRAS and HRA approval (IRAS ID:205986, REC:17/LO/0880); the third phase does not require ethics approval. Dissemination will be facilitated by project co-applicants with established connections to national policy making forums, in addition to publications, conference presentations and reports targeted to service providers and commissioners.